Effective Elimination of The Problems in Teaching The English 6-9 Grades Using Technological and Methodological Approaches - Gulbakhor Nazirkulova Muhitdin qizi (Bright Mind Publishing, 2025)
In this article, methods of effective and methodological approaches to gradual classes are used to effectively teach them through technological and methodological approaches, covering the English language effective methods of effective language and covering the modern technology used to study given.
Keywords: Language, English, language, education technology, project, interest, activity, interactive methods.